Preparation method of PET foam material based on maleic anhydride grafted polypropylene modified PET
Maleic anhydride grafting of polypropylene enhances PET foam's mechanical properties, addressing toughness and impact resistance issues, enabling its use in high-performance applications and supporting large-scale industrial production.
Patent Information
- Application Number
- CN202411428306.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
AI Technical Summary
Existing PET foam materials lack sufficient toughness and impact resistance, limiting their application in high-performance fields such as aerospace, automobile, and construction, and there is a need for environmentally friendly materials suitable for large-scale industrial production.
A method involving maleic anhydride grafting of polypropylene onto PET to enhance mechanical properties, using a process that includes mixing maleic anhydride grafted polypropylene with PET pellets and extruding with CO2 as a foaming agent to produce a PET foam sheet.
The modified PET foam exhibits improved mechanical properties, accelerated crystallization, and is suitable for large-scale industrial production with a simple, pollution-free process.
Smart Images

Figure CN119192653A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of PET polymer material preparation, and in particular relates to a method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET. Background Art
[0002] Polyethylene terephthalate (PET) foam material is a kind of light, uniformly structured insulating material with excellent physical properties and chemical stability, and is widely used in packaging, construction, automobile and other fields. With the development of industry and technology, the demand for high-performance materials is constantly increasing. Especially in the fields of aerospace, automobile, construction and packaging, light, high-strength, durable and environmentally friendly materials have become the focus of research and application. PET foam material has broad application prospects in these fields because of its excellent performance, and enhancing its toughness and impact resistance can make it be used in applications with higher performance requirements, expanding its application prospects. In order to enhance the toughness and impact resistance of PET, a method of co-modification is usually adopted, that is, by blending with other polymers or functionalized additives, to enhance the toughness and other physical properties of PET, and semi-crystalline polymers such as PET can improve its mechanical properties by accelerating the crystallization rate and improving the method of crystallinity. For this reason, the present invention is to improve the mechanical properties of PET material, and the upgrading research and development of technology is carried out. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the problem solved by the present invention is to provide a method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET, which has excellent mechanical properties, is environmentally friendly, has a simple process, has a wide range of uses, and is suitable for large-scale industrial production.
[0004] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET, the preparation steps are as follows:
[0006] S1. Maleic anhydride grafted polypropylene: Pour the solvent into a reaction vessel and start stirring at a low speed, then slowly add maleic anhydride and an initiator, raise the temperature and continue stirring until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution; then put the PP powder into a mechanical stirrer, start the stirrer, slowly add the prepared maleic anhydride solution, continue stirring to ensure uniform mixing, then put the mixture into a vacuum oven for drying, remove the solvent, and obtain a dry maleic anhydride and PP mixture; add the dried mixture into a twin-screw extruder, set the temperature and shear rate; under the action of high temperature and shear force, maleic anhydride and PP molecular chains react chemically to form a maleic anhydride grafted PP melt, which is extruded into strips through a die at the head of the extruder, and cooled and solidified in a cooling water tank; the solidified material is cut into uniform particles by a pelletizer, i.e. maleic anhydride grafted PP particles;
[0007] S2. Polypropylene modification: adding the maleic anhydride grafted PP particles prepared above to the PET pellets, and using a mechanical stirrer to uniformly mix the maleic anhydride grafted PP particles and the PET pellets;
[0008] S3, preparing PET foam material: adding the mixture in step S2 into the hopper of a supercritical foaming extruder, feeding it evenly into the extruder screw, using CO2 as a foaming agent for extrusion foaming, and finally cooling and molding to obtain a modified PET foam sheet.
[0009] Furthermore, in step S1, the initiator is dibenzoyl peroxide.
[0010] Furthermore, in step S1, the solvent is one of dichloromethane, tetrachloroethane, tetrahydrofuran, and anhydrous methanol.
[0011] Further, in step S1, 60 to 80 parts of solvent are poured into a reaction container and stirred at a low speed, then 20 parts of maleic anhydride and 1 part of initiator are slowly added, the temperature is raised to 40-45° C. and stirring is continued for 30 minutes until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution; then, 350 parts of 300 mesh PP powder are placed in a mechanical stirrer.
[0012] Furthermore, in step S1, the temperature of the twin-screw extruder is 180-200°C; the shear rate is 200-300 rpm; the grafting reaction time is 10-15 minutes; and the temperature of the cooling water tank is 15-25°C.
[0013] Furthermore, in step S2, maleic anhydride grafted PP particles are added to the PET pellets at a mass percentage of 0.5-1.5%.
[0014] Furthermore, in step S3, the temperature of the single screw in the extrusion foaming process is set to 250-260°C, and the temperature of the twin screw is set to 260-280°C; the amount of CO2 added to the PET extrusion foaming accounts for 0.5-0.8% of the total ratio; the speed of the single screw of the extruder is 80-120rpm; the speed of the twin screw of the extruder is 4-6rpm.
[0015] The chemical structures of maleic anhydride, PP and PET are as follows:
[0016]
[0017] The preparation route of maleic anhydride grafted PP is as follows:
[0018]
[0019] The structural formula of maleic anhydride grafted PP modified PET is as follows:
[0020]
[0021] The beneficial effects of the present invention are as follows:
[0022] 1. Polypropylene (PP) is a common thermoplastic polyolefin with excellent chemical resistance and mechanical properties, but its compatibility with PET is poor. In order to overcome this problem, the present invention grafts maleic anhydride (MAH) onto a polypropylene chain by a chemical grafting method to form maleic anhydride grafted polypropylene (PP-g-MAH). Maleic anhydride (MAH) is a bifunctional compound with high reactivity. When it is grafted onto a PP chain, it can provide a polar group to enhance the interfacial compatibility with PET; the anhydride group of PP-g-MAH can react with the terminal hydroxyl group in PET to modify PET; the present invention verifies through experiments that the modified PET can effectively shorten its crystallization induction time, increase the crystallization rate and crystallinity in the production process of PET foam materials, thereby achieving significant performance improvement in the modified PET foam materials.
[0023] 2. The alkane chain groups in the modified PP will provide heterogeneous nucleation sites in the PET polymer melt, reducing the energy barrier for the polymer melt to transform from a disordered state to an ordered crystalline state during cooling, thereby promoting the crystallization process and making the polymer chains orderly arranged at these sites to form crystal nuclei and gradually grow to form crystals, accelerating the crystallization rate, increasing the degree of crystallinity, and improving its mechanical properties.
[0024] 3. The process of the present invention is simple and easy to implement. The preparation method of the present invention has a simple process and can be implemented on conventional melt blending equipment, which is suitable for large-scale industrial production; the performance of the modified PET material is greatly improved, and it is suitable for a wider range of high-performance application fields; the modifier used is an environmentally friendly material, and the preparation process is pollution-free, which meets the requirements of sustainable development; the melt blending method has a simple process, is easy to realize large-scale production, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the testing direction of mechanical properties of PET foam materials.
[0026] Figure 2 This is the Fourier infrared spectrum of maleic anhydride grafted PP.
[0027] Figure 3 This is the DSC diagram of maleic anhydride grafted PP test. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0029] Example 1
[0030] First, pour 600 g of solvent dichloromethane into a 5L four-necked flask and start stirring at a low speed of 150 r / min. Then, slowly add 200 g of maleic anhydride and 10 g of initiator dibenzoyl peroxide. Raise the temperature to 42°C and continue stirring for 30 minutes until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution.
[0031] Then, 35,000 g of 300-mesh PP powder was placed in a mechanical stirrer, the stirrer was started, and the prepared maleic anhydride solution was slowly added. Stirring was continued for 30 minutes to ensure uniform mixing. Next, the mixture was placed in a vacuum oven for drying at a temperature of 45°C, a vacuum degree of -0.1 MPa, and a drying time of 4 hours. The solvent was removed to obtain a dry maleic anhydride and PP mixture.
[0032] The dried mixture was added to the twin-screw extruder, and the temperature of the twin-screw extruder was set to 185°C and the shear rate to 270rpm. The time from the initial feeding into the extruder to the discharge of the die head was 14 minutes, and the maleic anhydride grafted PP melt was extruded into strips through the die at the head of the extruder, and then pulled into a cooling water tank for cooling and solidification. The water temperature of the cold water tank was 21°C. The solidified material was cut into uniform particles by a pelletizer, namely maleic anhydride grafted PP particles.
[0033] Add maleic anhydride grafted PP particles to PET at a mass ratio of 0.5%, and use a mechanical stirrer to evenly mix the maleic anhydride grafted PP particles and PET pellets. Then, add the mixture to the hopper of the supercritical foaming extruder and evenly feed it into the extruder screw. During the extrusion foaming process, the temperature of the single screw is set to 255°C, and the temperature of the twin screw is set to 270°C; the amount of CO2 added to PET extrusion foaming accounts for 0.6% of the total ratio; the speed of the single screw of the extruder is preferably 90rpm; the speed of the twin screw of the extruder is preferably 4rpm. Finally, cool and shape to obtain the modified PET foam sheet.
[0034] Example 2
[0035] First, pour 700 g of solvent dichloromethane into a 5L four-necked flask and start stirring at a low speed of 150 r / min. Then, slowly add 200 g of maleic anhydride and 10 g of initiator dibenzoyl peroxide. Raise the temperature to 44°C and continue stirring for 30 minutes until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution.
[0036] Then, 35000g of 300 mesh PP powder was placed in a mechanical stirrer, the stirrer was started, and the prepared maleic anhydride solution was slowly added. Stirring was continued for 30 minutes to ensure uniform mixing. Next, the mixture was placed in a vacuum oven for drying at a drying temperature of 45°C, a vacuum degree of -0.1MPa, and a drying time of 5h. The solvent was removed to obtain a dry maleic anhydride and PP mixture.
[0037] The dried mixture was added to the twin-screw extruder, and the temperature of the twin-screw extruder was set at 190°C and the shear rate was set at 280rpm. The time from the initial feeding into the extruder to the discharge of the die head was 12 minutes, and the maleic anhydride grafted PP melt was extruded into strips through the die at the head of the extruder, and then pulled into a cooling water tank for cooling and solidification. The water temperature of the cold water tank was 22°C. The solidified material was cut into uniform particles by a pelletizer, namely maleic anhydride grafted PP particles.
[0038] Add maleic anhydride grafted PP particles to PET at a mass ratio of 1%, and use a mechanical stirrer to evenly mix the maleic anhydride grafted PP particles and PET pellets. Then, add the mixture to the hopper of the supercritical foaming extruder and evenly feed it into the extruder screw. During the extrusion foaming process, the temperature of the single screw is set to 258°C, and the temperature of the twin screw is set to 275°C; the amount of CO2 added to PET extrusion foaming accounts for 0.7% of the total ratio; the speed of the single screw of the extruder is preferably 100rpm; the speed of the twin screw of the extruder is preferably 5rpm. Finally, cool and shape to obtain the modified PET foam sheet.
[0039] Example 3
[0040] First, pour 750 g of solvent dichloromethane into a 5L four-necked flask and start stirring at a low speed of 150 r / min. Then, slowly add 200 g of maleic anhydride and 10 g of initiator dibenzoyl peroxide. Raise the temperature to 45°C and continue stirring for 30 minutes until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution.
[0041] Then, 35000g of 300 mesh PP powder was placed in a mechanical stirrer, the stirrer was started, and the prepared maleic anhydride solution was slowly added. Stirring was continued for 30 minutes to ensure uniform mixing. Next, the mixture was placed in a vacuum oven for drying at a drying temperature of 45°C, a vacuum degree of -0.1MPa, and a drying time of 8h. The solvent was removed to obtain a dry maleic anhydride and PP mixture.
[0042] The dried mixture was added to a twin-screw extruder, and the temperature of the twin-screw extruder was set at 200°C and the shear rate was set at 300rpm. The time from the initial feeding into the extruder to the discharge from the die head was 11 minutes, and the maleic anhydride grafted PP melt was extruded into strips through the die at the head of the extruder, and then pulled into a cooling water tank for cooling and solidification. The water temperature of the cold water tank was 24°C. The solidified material was cut into uniform particles by a pelletizer, namely maleic anhydride grafted PP particles.
[0043] Add maleic anhydride grafted PP particles to PET at a mass ratio of 1.5%, and use a mechanical stirrer to evenly mix the maleic anhydride grafted PP particles and PET pellets. Then, add the mixture to the hopper of the supercritical foaming extruder and evenly feed it into the extruder screw. During the extrusion foaming process, the temperature of the single screw is set to 258°C, and the temperature of the twin screw is set to 280°C; the amount of CO2 added to PET extrusion foaming accounts for 0.8% of the total ratio; the speed of the single screw of the extruder is preferably 110rpm; the speed of the twin screw of the extruder is preferably 6rpm. Finally, cool and shape to obtain the modified PET foam sheet.
[0044] In the above embodiments, all the raw materials used are commercially available products, among which 300 mesh PP powder is general-purpose grade, brand Lubrizol of Germany, grade MP1200.
[0045] In the embodiment, the maleic anhydride grafted PP modified PET prepared by the present invention was used for foaming, and the produced PET foam sheet was subjected to three square performance tests. The test directions are as follows: Figure 1 shown.
[0046] The specific data are shown in the following table:
[0047] Table "1" Example 1-3 Test of the mechanical properties of maleic anhydride grafted PP on PET extrusion foaming
[0048]
[0049]
[0050] It can be clearly seen from the data in Table 1 that maleic anhydride grafted PP can improve the mechanical properties of PET extruded foam board to a certain extent by modifying PET; within the range of 0.5-1.5%, as the addition amount of maleic anhydride grafted PP increases, the mechanical properties of the foam board in three directions are improved, indicating that the maleic anhydride grafted PP prepared by the present invention has a good effect in the PET modification process.
[0051] from Figure 2 It can be seen that the grafted product has a weak anhydride characteristic absorption peak at 1711.002cm-1, indicating that maleic anhydride has been successfully grafted onto the PP macromolecular chain.
[0052] from Figure 3 It can be seen that for the modified PET, within the range of 0.5-1.5%, as the amount of maleic anhydride grafted PP added increases, the overall temperature of the crystallization temperature range increases, indicating that in the cooling molding stage after PET is extruded and foamed by the die head mold of the supercritical foaming extruder, as the amount of maleic anhydride grafted PP added increases, the crystallization time of PET is advanced; for the blank group samples, the temperature needs to drop to 78.3℃ before PET will crystallize in large quantities, indicating that maleic anhydride grafted PP can effectively shorten the crystallization induction time of modified PET and increase the crystallization rate.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET, characterized in that: The preparation steps are as follows: S1. Maleic anhydride grafted polypropylene: Pour the solvent into a reaction vessel and start stirring at a low speed, then slowly add maleic anhydride and an initiator, raise the temperature and continue stirring until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution; then put the PP powder into a mechanical stirrer, start the stirrer, slowly add the prepared maleic anhydride solution, continue stirring to ensure uniform mixing, then put the mixture into a vacuum oven for drying, remove the solvent, and obtain a dry maleic anhydride and PP mixture; add the dried mixture into a twin-screw extruder, set the temperature and shear rate; under the action of high temperature and shear force, maleic anhydride and PP molecular chains react chemically to form a maleic anhydride grafted PP melt, which is extruded into strips through a die at the head of the extruder, and cooled and solidified in a cooling water tank; the solidified material is cut into uniform particles by a pelletizer, i.e. maleic anhydride grafted PP particles; S2. Polypropylene modification: adding the maleic anhydride grafted PP particles prepared above to the PET pellets, and using a mechanical stirrer to uniformly mix the maleic anhydride grafted PP particles and the PET pellets; S3, preparing PET foam material: adding the mixture in step S2 into the hopper of a supercritical foaming extruder, feeding it evenly into the extruder screw, using CO2 as a foaming agent for extrusion foaming, and finally cooling and molding to obtain a modified PET foam sheet.
2. The method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET according to claim 1, characterized in that: In the step S1, the initiator is dibenzoyl peroxide.
3. The method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET according to claim 1, characterized in that: In the step S1, the solvent is one of dichloromethane, tetrachloroethane, tetrahydrofuran, and anhydrous methanol.
4. The method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET according to claim 1, characterized in that: In the step S1, 60-80 parts of solvent are poured into a reaction container and stirred at a low speed, then 20 parts of maleic anhydride and 1 part of initiator are slowly added, the temperature is raised to 40-45° C. and stirring is continued for 30 minutes until the maleic anhydride and the initiator are completely dissolved to obtain a maleic anhydride solution; then, 350 parts of 300 mesh PP powder are placed in a mechanical stirrer.
5. The method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET according to claim 1, characterized in that: In the step S1, the temperature of the twin-screw extruder is 180-200°C; the shear rate is 200-300 rpm; the grafting reaction time is 10-15 minutes; and the temperature of the cooling water tank is 15-25°C.
6. The method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET according to claim 1, characterized in that: In the step S2, maleic anhydride grafted PP particles are added to the PET pellets at a mass ratio of 0.5-1.5%.
7. The method for preparing a PET foam material based on maleic anhydride grafted polypropylene modified PET according to claim 1, characterized in that: In step S3, the temperature of the single screw during the extrusion foaming process is set to 250-260°C, and the temperature of the twin screw is set to 260-280°C; the amount of CO2 added to the PET extrusion foaming accounts for 0.5-0.8% of the total ratio; the speed of the single screw of the extruder is 80-120rpm; the speed of the twin screw of the extruder is 4-6rpm.
Citation Information
Cited By
Polymer foam and preparation method thereof
CN121045444A